A case study examining the organizational change process in a private company - Ahmad Puzi, Fara Wahiza (2021)
The primary purpose of this study is to investigate the organizational change process in a private company. In the property industry, there is a demand for improvement and developers know they have to step out of their comfort zone, be flexible, and adapt to the homebuyers’ ever-changing wants and needs. The company repositioned itself by moving away from the traditional way to the present trends. There is limited research on employees' readiness to accept change in an organization. This study-appraised change from the perspective of the employees and how they understand the change process. This study is a single case study on a construction company. The company’s leadership decided to use Lewin's change theory as a guide for the change initiative. This helps address the uncertainty and resistance to change experienced at all staff levels within the company. The primary informants for the study range from executives to senior managers from fourteen (14) departments. The results from the interviews conducted discover variances and changes in employees' working styles. The results can be grouped under nine different themes. The themes are: Theme One: Need for Change; Theme Two: Resistance to Change; Theme Three: Perception Towards Change and Transformation; Theme Four: Reaction Towards Change; Theme Five: Organizational Culture; Theme Six: Communication; Theme Seven: Leadership Effectiveness; Theme Eight: Participation in Change and Theme Nine: Performance. Informants stressed that good and strong leadership is compulsory to ensure an effective organizational culture. Leadership is also key in handling problematic and challenging team members. There is a positive impact of leadership style on the change process in terms of employee involvement, employee motivation as well as knowledge sharing at the individual and organizational levels. Organizations should take the time for deliberation, reflection, and experimentation in approaching planned change and recognize that all evidence-based principles will require local adaptation and adjustment. The goals of employees and the employer should be in tandem to ensure that the change initiatives are accepted and supported.